Duties and Functions of the Security Intelligence Unit Blora Police in Efforts to Overcome - Abdul Kirom; Edi Pranoto (CV. Publikasi Indonesia, 2023)
This article discusses the role of the Police Security Intelligence Unit in maintaining security and helping uncover criminal acts. The study focuses on the duties and functions of the Blora Police Security Intelligence Unit, as well as the obstacles it faces in carrying out its duties. The research concludes that the Blora Police Satintelkam faces several obstacles due to the insufficient number of personnel and lack of necessary facilities. The article suggests that the Blora Police should consider adding more personnel to the Satintelkam and improving its facilities to make it more effective in tackling crime in the Blora Regency area.